Optimasi formula gel ekstrak kubis ungu (Brassica Oleracea L. Var. Capitata F. Rubra) menggunakan simplex lattice design dan pengujian aktivitas antioksidan secara in vitro - Senja, Rima Yulia; Nugroho, Akhmad Kharis; Setyowati, Erna Prawita (Pharmaciana, 2016)
ABSTRACTA study of optimization of red cabbage (Brassica oleracea.L. var. capitata f. rubra) gel extract formula has been performed by using Simplex Lattice Design (SLD) method and antioxidant activity of the formula gel was also evaluated by using in vitro method.The red cabbage was extracted by soxhletation by using ethanol 96% followed by optimization of red cabbage extract in antioxidant gel preparation used SLD method by Design-Expert® software version 7 (DX7) and determination of its IC50 used UV-Spectrophotometry. The stability of optimum gel formula is seen through comparison of physycal properties at the beginning and after four weeks storage used ANOVA, with a 95% significant level. Optimum gel formula of red cabbage extract obtained in the proportion of Metolose 3,883%, propilen glikol 13.5%, Tween 80 1.117%. The evaluation results of optimum gel formula of red cabbage extract is the surface area of gel dispersive of 38.99 ± 3.27cm2; viscosity gel dPa.s of 295.56 ± 1.93 and viscosity change 3.89 ± 0.96%. From the results of statistical analysis of one t-test sample was concluded that there was no difference between the prediction price of software with the observation result (p> 0.05). The IC50 test result of the optimum formula of red cabbage extract gel was 257.25 ± 0.35 µg / mL. The testing result of the physical stability of the optimum formula of red cabbage extract gel suffered a pH decrease after 4 weeks of storage (p <0.05).